2019
DOI: 10.21873/anticanres.13232
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Evaluation Method for FOXP3+ Tregs and CD8+ T-cells in Breast Carcinoma: Association With Breast Carcinoma Subtypes, Stage and Prognosis

Abstract: Background/Aim: The role of FOXP3+ Tregs and CD8+ T-cells in different stages and subtypes of breast carcinoma (BC) is yet to be fully defined, mainly because of methodological variations between studies. The aim of this study was to assess FOXP3+ and CD8+ intratumoral stromal TILs (sTILs) by a standardized method, in order to discern differences between the histological subtypes and BC stage and evaluate the applicability of the method. Patients and Methods: FOXP3+ and CD8+ sTILs were studied immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…A high proportion of infiltrated Tregs in RCC may therefore indicate a worse outcome, which is similar to the CIBERSORT findings from the present study. Furthermore, the present study demonstrated that the proportion of Tregs was associated with tumor grade and TNM classification, which was also the case for other cancer types (34,35). In addition, the results from IHC demonstrated that FOXP3 expression in Tregs was increased in RCC samples compared with that in adjacent tumors.…”
Section: Discussionsupporting
confidence: 82%
“…A high proportion of infiltrated Tregs in RCC may therefore indicate a worse outcome, which is similar to the CIBERSORT findings from the present study. Furthermore, the present study demonstrated that the proportion of Tregs was associated with tumor grade and TNM classification, which was also the case for other cancer types (34,35). In addition, the results from IHC demonstrated that FOXP3 expression in Tregs was increased in RCC samples compared with that in adjacent tumors.…”
Section: Discussionsupporting
confidence: 82%
“…They found that TNBC patients with a high CD8 + TILs level or high CD8/Foxp3 ratio in residual tumors exhibit significantly favorable recurrence-free survival (RFS) and breast cancer-specific survival (BCSS) [101]. Another study also showed that CD8 + TILs were related to favorable DMFS, DFS, and BCSS in the entire 207 breast cancer group and in 56 TNBC group [102]. BRCA1-IRIS overexpressing (IRISOE) TNBC carcinomas had more CD25 + /Foxp3 + Tregs and few CD8 + /PD-1 + cytotoxic T-cells, which showed that the interaction between macrophages and IRISOE cells initiated an immunosuppressive TME within TNBC tumors [71].…”
Section: Cd8 + Tilsmentioning
confidence: 98%
“…The latter knowledge in combination with perceiving the cancer -immunity cycle, has led numerous studies to focus on the tumor microenvironment of the host in several solid cancers, including IBC (15,16). Over the decades, it has been proven that the presence of high tumor infiltrating lymphocytes (TILs) in solid tumors, such as lung, ovarian cancer, colorectal cancer, renal cell carcinoma, prostate cancer and head and neck cancers, as well as in breast cancer, is associated with better prognosis (17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%